University Students' Attitudes Towards E-Learning - Audronė Dumčienė; Tomas Saulius; Audrius Čapskas (Lithuanian Sports University, 2018)
Background. E-learning is a new paradigm of modern teaching methods. The aim of the paper was to reveal the university students' attitudes towards e-learning. Methods. Research sample involved undergraduate (first cycle) and postgraduate (second cycle) students of three different universities, 156 men and 278 women. Questionnaire was comprised of 60 questions and statements. Results. Research reveals that 40% of undergraduates and 42% of postgraduates positively treat e-learning as the method of study content presentation; 23% of undergraduate and 38% postgraduate students believe that study content presented in e-learning environment helps them focus attention; 61% of the undergraduates and 59% of postgraduate students claim that materials accessible in e-learning environment are relevant to their studies. Even 37%  of  undergraduates  and  34%  of  postgraduates  are  completely  satisfied  with  their  study  results  achieved  by studying materials presented in e-learning environment. Attitudes of male and female students and students from different universities differ significantly (p < .05). About 40% of undergraduate and 36% of postgraduate students believe that studying via e-learning is easier than studying based on traditional methods, 48% and 44% respectively think that it is harder. The majority, i.e. 59% of undergraduates and 52% of postgraduates, prefer blended learning methods. About 42% of first cycle students and 43% of second cycle students disagree or partly disagree with the claim that studies via e-learning and studies based on traditional methods do not differ in respect of their quality; 38% of undergraduate and 42% of postgraduate students believe that e-learning and traditional methods lead to the acquisition of the same competences. Students who have part-time jobs and students who have full-time jobs have significantly different (p < .05) attitudes towards competences acquired via e-learning and via traditional methods. The opinion that the same competences are acquired via e-learning and via traditional methods is more common among full-time workers. Students (45% of undergraduates and 37% of postgraduates) tend to believe that in the e-learning environment studies were organized as professionally, qualitatively and effectively as studies based on traditional methods. This view is opposed by 22% of undergraduate and 30% of postgraduate students. Conclusions.  Students  treat  traditional  ("live")  lectures  more  favourably  than  autonomous  studies  in  the e-learning environment. They tend to believe that the blended learning method is the most acceptable. Male students' and female students' attitudes towards study results in the e-learning environment differ significantly. The majority believe that competences acquired via e-learning and the ones acquired via traditional methods do not differ. Keywords:  undergraduate students, postgraduate students, e-learning, traditional study methods